2016
DOI: 10.1017/s1751731115003006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response to dietary fibre composition in horses

Abstract: The hypothesis for this study was that a higher dietary proportion of soluble fibre would result in stable and constant plasma metabolite and regulatory hormone concentrations. The study was a 4 × 4 Latin Square design with a sequence of 17 days adaptation to the ration followed by 8 sampling days. The feed rations consisted of only timothy hay (H), hay plus molassed sugar beet pulp combined with either whole oats (OB) or barley (BB) and hay plus a loose chaff-based concentrate (M). Four horses were fitted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In particular, the major end‐products of the gut microbiota catabolism of dietary fibre, i.e. the short‐chain fatty acids acetate, propionate and butyrate, represent a key energy source for the horse, accounting for more than 50% of the total daily animal requirement . The relevance of the gut microbial ecosystem in horse physiology is also highlighted by the deleterious impact of several gut microbiota‐compromising factors on the horse health, such as antimicrobial administration, dietary changes or gastrointestinal infections .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the major end‐products of the gut microbiota catabolism of dietary fibre, i.e. the short‐chain fatty acids acetate, propionate and butyrate, represent a key energy source for the horse, accounting for more than 50% of the total daily animal requirement . The relevance of the gut microbial ecosystem in horse physiology is also highlighted by the deleterious impact of several gut microbiota‐compromising factors on the horse health, such as antimicrobial administration, dietary changes or gastrointestinal infections .…”
Section: Introductionmentioning
confidence: 99%
“…For example, production of short-chain fatty acids (SCFA) from the microbial digestion of cellulose provides a substantial portion of the daily energy requirements of a horse. While SCFAs are well-recognized for their effects on host mucosal health and maintenance of mucosal homeostasis, they represent a small fraction of the thousands of metabolites produced by the microbiota each day, many of which also have important impact on host health [24]. Despite the importance of the intestinal microbiota for equine health and availability of molecular techniques for assessing this complex microbial community, information regarding the quantification, characterization, and metabolic activity of the equine gastrointestinal microbiota is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Through fermentation, the fibrous components are degraded to monosaccharides. The anaerobic environment of the hindgut prevents the complete oxidation of monosaccharides and instead produces VFA, acetate, propionate, and butyrate [ 45 ]. The results from previous studies indicated that changing the energy source from starch-rich feeds to high-fiber feeds in training horses changes the muscle energy supply from glucose to acetic acid due to increased fermentation in the hindgut [ 46 ] and the acetate/propionate ratio increases when the forage/concentrate ratio increases [ 47 ].…”
Section: Discussionmentioning
confidence: 99%